Linear Programming as a Tool for Managing the Training Process of Esports Teams - Oksana Shynkaruk; Nataliia Byshevets; Alla Aloshyna; Olena Iakovenko; Kostiantyn Serhiienko; Valerii Pinchuk; Oleksandr Petryk; Ivan Lut (Physical Education Theory and Methodology)
Background. Linear programming, with its ability to account for multiple constraints and optimize linear objective functions, is a promising tool for solving training planning tasks. This method enables the development of individualized plans tailored to the specific goals of each player and the team as a whole.